LESSON LEARNT FROM KREDIT TRIGUNA: THE HOUSING FINANCE FOR LOW-INCOME COMMUNITY - Dyah Widi Astuti (Universitas Muhammadiyah Surakarta, 2015)
Financial aid or loan designed specifically for housing the low income community,especially they are working in informal sector, is necessary. To answer the need, abouttwo decades ago, Bank Tabungan Negara (BTN) or The State Savings Bank hadintroduced a loan package, named Kredit Triguna. Designed as a mixed microcreditpolicy, this loan implemented a fully concept of integrated approach. But it was onlyavailable for two years, and then discontinued. As one of the best practice microfinanceprograms at the time, this condition was considered as a unique case. This paper aimsto evaluate the previous microcredit policy, that was Kredit Triguna, in its implementation and to identify reasons for its success or failure in performance. As a sample of case study, a project of housing redevelopment in Kalianyar riverbank, Mojosongo, Surakarta using the loan is observed. The result of the study will help in developing new alternative scheme in housing finance for the low-income community.